Emicizumab for the Treatment of Acquired Hemophilia A: Consensus Recommendations from the GTH-AHA Working Group - Pfrepper, Christian; Klamroth, Robert; Oldenburg, Johannes; Holstein, Katharina; Eichler, Hermann; Hart, Christina; Moehnle, Patrick; Schilling, Kristina; Trautmann-Grill, Karolin; Alrifai, Mohammed; Ay, Cihan; Miesbach, Wolfgang; Knoebl, Paul; Tiede, Andreas (Hämostaseologie, 2023)
Background Acquired hemophilia A (AHA) is a severe bleeding disorder caused by autoantibodies against coagulation factor VIII (FVIII). Standard treatment consists of bleeding control with bypassing agents and immunosuppressive therapy. Emicizumab is a bispecific antibody that mimics the function of activated FVIII irrespective of the presence of neutralizing antibodies. Recently, the GTH-AHA-EMI study demonstrated that emicizumab prevents bleeds and allows to postpone immunosuppression, which may influence future treatment strategies.Aim To provide clinical practice recommendations on the use of emicizumab in AHA.Methods A Delphi procedure was conducted among 33 experts from 16 German and Austrian hemophilia care centers. Statements were scored on a scale of 1 to 9, and agreement was defined as a score of ≥7. Consensus was defined as ≥75% agreement among participants, and strong consensus as ≥95% agreement.Results Strong consensus was reached that emicizumab is effective for bleed prophylaxis and should be considered from the time of diagnosis (100% consensus). A fast-loading regimen of 6 mg/kg on day 1 and 3 mg/kg on day 2 should be used if rapid bleeding prophylaxis is required (94%). Maintenance doses of 1.5 mg/kg once weekly should be given (91%). Immunosuppression should be offered to patients on emicizumab if they are eligible based on physical status (97%). Emicizumab should be discontinued when remission of AHA is achieved (97%).Conclusion These GTH consensus recommendations provide guidance to physicians on the use of emicizumab in AHA and follow the results of clinical trials that have shown emicizumab is effective in preventing bleeding in AHA.
Keywords: acquired hemophilia; emicizumab; prophylaxis; recommendation; consensus